DIAGNOSE AND MANAGEMENT TINEA FASCIALIS - Suryantara P, I Pt Agus; Rusyati, L.M; Darmada, I.G.K (E-Jurnal Medika Udayana, 2014)
Fungi disease  on skin is often occur at Indonesia because it is a tropic country that has hot climate and also correlate wit bad hygiene.  Dermatofitosis is fungi disease on the keratinizing tissue and differentiate as many class such as Tinea Corporis or Tinea Cruris. Tinea fascialis include in this form. The diagnose this disease from anamnesis, clinical manifetation, and also test result from the tissue. Management for this tineacomprise to topical and systemic. The important one in management this disease is prevention  management include in control of skin dryness.
Keywords: Tinea, Fasialis